Analysis Of Factors Causing Repetition Of Computed Radiography Images In An Effort To Improve The Quality Of Health Services In Radiology - Widiatmoko, Mahfud Edy; Sari, Nur Alifa Purnama (OJS Universitas Muhammadiyah Gresik, 2025)
Radiology is a vital component of healthcare services in hospitals, aimed at assisting diagnoses through radiographic imaging using X-rays. To ensure optimal image quality, a quality assurance program is implemented. One of the objectives of this program is to minimize the repetition of radiological examinations. Therefore, a reject analysis of radiographic images is conducted to identify the causes and reasons for repeated imaging. This research aims to analyze the factors contributing to repeated computed radiography (CR) images to improve the quality of radiology health services. It is a quantitative descriptive study conducted through observation to determine the percentage of image repetitions and identify the causes. The data was analyzed using the repeat rate formula to calculate the repetition percentage systematically. The study took place from February to April 2024, with a total of 8,197 CR images, of which 410 were repeated. Results: The quality of radiology services is categorized as good, based on a monthly image repetition rate of 1.75%, which is within the acceptable limit of ≤2% as per the Indonesian Ministry of Health Regulation No. 129/Menkes/SK/II/2008 on minimum hospital service standards.